Future Studies in Arab Thought: Reality and Challenges - Al-Ali, Abdullah bin Fureh Muaqil (The Arab Journal of Administration, 2025)
This study reviewed the problem of the term “future studies” in Arab thought. The study clarified the reality of future studies in Arab thought, and revealed the challenges facing the dissemination of the culture of future studies in addition to reviewing and analyzing the problems and challenges related to the Arab future. The study focused on the application of future studies in the Arab world by summarizing the most important Arab experiences in the application of future studies. The study used analytical descriptive approach that relies on describing the phenomenon based on logic by literature review and scientific studies related to the subject of “future studies” and the reality of its application in the Arab world and its obstacles. The study reached several conclusions such as : One of the most important problems facing” future studies” in the Arab world is the lack of interest in it and the lack of recognition of its importance and impact in determining the future paths of the region. The term “future studies” has a non-Arabic origin and has been translated in several forms and meanings into Arabic, which resulted in the reactions of many writers and thus their classification of it and its importance, and future studies suffer from deficiencies in its application. Attempts are almost exclusively on the academic side with almost complete disconnection from reality and its challenges. The most significant obstacle to the dissemination of the culture of future studies in the Arab world is that the first prospects set by Arabs for themselves were practically inapplicable. The study reached many challenges related to the Arab future, including the future of the Arab-Israeli conflict, the future of relations with neighboring countries and the future of the Arab regime, and that there are successful experiences in the Arab world through visions and future studies presented by some Arab States as role models. The study recommended unifying the basic concepts about the term “future studies” within an Islamic and Arab vision, establishment and activation of more think tanks concerned with future studies that support the making and decision-making in the Arab world, urging decision-makers and politicians in Arab world governments to increase interest in the results of future and forward-looking studies related to the future of the countries of the Arab world, and to provide support for unifying efforts to establish entities, think tanks and joint research teams from all Arab countries.